2021
DOI: 10.4149/km_2017_4_237
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Si content on machinability of Al-Si alloys

Abstract: This study investigates the effect of the change in the amount of Si found in Al-Si alloys on mechanical properties and machinability properties of the alloy. The way the microstructure and the mechanical properties change depending on the increase in the %Si amount in the alloy and the effects of such changes on Flank Build-up (FBU), wear in the cutting edge, surface roughness, and machinability were analysed. To this end, alloys with varying amounts of silicon (i.e., 2 to 12 wt.% Si) were used in the study. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…5b), where the signal peaks of ZnO (002) and Al can be observed, indicates that the prepared ZnO film has a single-crystal structure. 16,17 The devices were fabricated with different PI film thicknesses, and their electrical properties were measured in flat and curved states. Figure 6a shows a photograph of the device in the flat state.…”
Section: Resultsmentioning
confidence: 99%
“…5b), where the signal peaks of ZnO (002) and Al can be observed, indicates that the prepared ZnO film has a single-crystal structure. 16,17 The devices were fabricated with different PI film thicknesses, and their electrical properties were measured in flat and curved states. Figure 6a shows a photograph of the device in the flat state.…”
Section: Resultsmentioning
confidence: 99%
“…The axial component of cutting force became significantly higher when turning hypoeutectic Al−Si alloys with higher Si content, while the tangential component of cutting force was hardly affected by the Si content. 26 Akyüz 27 also reported that the decreased cutting forces with the increase in Si content lead to an improvement of machinability in machining hypoeutectic Al−Si alloys. In fact, transformation of coarse silicon particles to fine fibrous structure enhances the machinability of hypoeutectic Al−Si alloys by exhibiting the lowest BUE.…”
Section: Introductionmentioning
confidence: 96%
“…The reason can be attributed to the reduction of BUE at high cutting speeds. 27 Farid et al 29 indicated that the uncontrollable thrust force should be addressed to have full benefits of high-speed drilling of Al−Si alloys. The results indicated that cutting speed had the highest contribution to thrust force.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Akyüz [ 16 ] reported that cutting efficiency was improved in Al-13%Si alloys containing 0.2~0.4%Sn; thus, the cutting resistance was decreased, the cutting temperature was lowered, and the progress of tool wear was retarded. The improvement in machined surfaces was not clearly defined, although the treatment of chips became easier because their shape had changed to a sheared form.…”
Section: Introductionmentioning
confidence: 99%